Associations of Ambient Air Pollutant Concentrations With Respiratory Symptoms and Perceived Health Status in Japanese Adults With and Without Chronic Respiratory Diseases: A Panel Study - Motoyuki Nakao; Keiko Yamauchi; Satoshi Mitsuma; Tetsuro Odaira; Hideto Obata; Yoichi Chijimatsu; Yoko Ishihara
Objectives In recent years, transboundary air pollution from mainland East Asia has led to growing concerns about air pollution in Japan. Air pollution is reportedly associated with the exacerbation of respiratory diseases. In this study, we assessed the effects of air pollution on respiratory symptoms and the health status of participants with and without chronic respiratory diseases. Methods Participants (n=2753) with and without chronic respiratory diseases who visited healthcare facilities in Japan during February from 2010 to 2015 filled out a self-report questionnaire regarding their symptoms and perceived health status. Participants were followed up during April-May and June-July. Results Oxidant concentrations were associated with respiratory symptoms, overall health, and quality of life (QoL). Suspended particulate matter (SPM) and particulate matter <2.5 μm levels were associated with physical fitness; SPM was also associated with QoL. Recent experience of an Asian sand dust event had a significant effect on allergic symptoms, change in health, and QoL. Conclusions Respiratory symptoms were more strongly affected by oxidants than by other pollutants. Significant associations of air pollutants were found with a comprehensive range of items related to perceived health status, including overall health and QoL. Although the effects of air pollutants on respiratory symptoms and health status were more apparent among patients with respiratory diseases, the adverse effects of air pollutants were significant even among participants without such conditions.